Perencanaan Pendidikan Islam Untuk Meningkatkan Mutu Layanan Pendidikan - hakim, abd (FATAWA: Jurnal Pendidikan Agama Islam, 2021)
The purpose of this study is to find a model of the concept of Islamic education planning, with the hope that it can be useful for management science and Islamic education management. In this study, the researcher used a qualitative descriptive research method with data sources from the library (library research) and the main data sources were the Qur'an, interpretations, hadith, Islamic history books and books related to educational planning. Studies on planning and planning for education conventionally have been widely discussed and written by experts, but studies on planning and planning for education in an Islamic perspective are still not many. The findings of this study are as follows: (1) Curriculum planning refers to national curriculum standards and is implemented by determining subjects and scheduling implementation. (2) Curriculum development is carried out by adding religious subjects based on Nahdatul Ulama and giving authority to teachers to develop learning methods (3) Planning for learning resources is carried out by preparing textbooks and student worksheets and preparing libraries (4) Planning for facilities and infrastructure is carried out by prepare basic facilities and infrastructure which is carried out by needs analysis. (5) The principal plans for teaching staff to adapt to the needs and must have a bachelor's status. Educational staff planning is applicable. (6) Teacher performance planning is carried out through the preparation of performance standards that contain the main tasks and functions of educators and education staff.